KESANTUNAN BERBAHASA PADA CRITA CÊKAK DALAM MAJALAH JAYA BAYA SEBAGAI MATERI AJAR BAHASA JAWA DI SEKOLAH MENENGAH PERTAMA - Pribadi, Nirbito Hanggoro; Sumarwati, Sumarwati; Kurwidaria, Favorita (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2018)
The aims of this research was to identify the language politeness on short story in Crita Taman Putra rubric of Jaya Baya magazine as subject matters of Javanese in Junior High School at writing dialog involving parent’s basic competence. The result of this research concluded as follows: (1) the being maxim of language politeness of short story in Crita Taman Putra rubric of Jaya Baya magazine covering six maxims such as used maxim of wisdom, maxim of generosity, maxim of appreciation, maxim of simplicity, maxim of consensuality, and maxim of sympathy; (2) the background of the language politeness behaviour that was used in short story in Crita Taman Putra rubric of Jaya Baya magazine caused by four factors. Those were respect older people, respect people in the same age, teach and respect younger people, and match perception with other people; (3) short story in Crita Taman Putra rubric of Jaya Baya magazine relevance as subject matters with some supporting factors such as the used of language were understandable, the use of vocabulary that suitable with Javanese, and contain character education values.